A compact dual‐band superconducting filter with fine‐tuning coupling structure. Issue 1 (4th November 2020) - Lu, Xinxiang; Guo, Xubo; Luo, Chenjie; Wei, Bin; Cao, Bisong
Abstract: A novel dual‐mode optimized patch capacitor loaded T‐type resonator is proposed for the design of a dual‐band filter (DBF). The resonator has its lowest even‐ and odd‐mode at the two expected passband frequencies and the first spurious mode far away from the passbands. For tuning of the two sets of coupling strengths for both passbands, open/shorted secondary coupling structures are introduced as a fine‐tuning coupling structure to increase/decrease the primary coupling strength. A four‐pole DBF with passbands centered at 2450 and 3500 MHz, respectively, is proposed and fabricated using the HTS material. The measured results of the filter indicate superior performance and good fitting with the simulation results. The return losses of both passbands and the insertion losses obtained by measurements are greater than 14 dB and less than 0.3 dB, respectively. The stopband rejection exceeds 50 dB up to 8.0 GHz.